Researches on the Influence of Blasting of Newly Built Tunnel on the Existing Tunnel Structure with Small Cross Angle - Xian Du; Qinghua Xiao; Congming Li; Qiang Xiong; Jianyou Yu (Advances in Civil Engineering)
In recent years, with the increasement of the railway expansion projects, the blasting damage has caused great threat to the safety of the existing tunnel structure. However, few researches are carried out on the influence of tunnel blasting construction on existing small-angle crossing tunnel structure. In this study, the dynamic response of existing tunnel structure to the blasting activities in newly built tunnel is analyzed by numerical simulation. From the comparison of vibration velocity, lining stress, and the displacement of the existing tunnel structure, the blasting methods, surrounding rock condition, cross angle, and clear distance are proven to be the highly correlated factors for the dynamic response of the existing tunnel to blasting. Then, combined with the analytic hierarchy process, the vibration velocity is selected as the optimal index to indicate the dynamic response to blasting activities.